2013
DOI: 10.1080/1359432x.2013.787183
|View full text |Cite
|
Sign up to set email alerts
|

Exploring business travel with work–family conflict and the emotional exhaustion component of burnout as outcome variables: The job demands–resources perspective

Abstract: Research on the relations among business travel, work, and family domains has been limited. To address this issue, this study examined the influence of business travel on work-family conflict and the emotional exhaustion component of burnout, using the Job Demands-Resources perspective. The study was conducted in a large Norwegian oil and gas company, and to overcome the limitations of self-reported data on business travel frequency, the company's business travel database was utilized in the study. The respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 53 publications
9
67
1
3
Order By: Relevance
“…In addition, having children and being young increased travelers' WFC to some extent. These results are also in line with an earlier study concerning business 804 CDI 19,7 travelers ( Jensen, 2013) and others affected by WFC in general ( Jansen et al, 2003;Kinnunen et al, 2004). Furthermore, WFC was at a lower level among travelers who exercised regularly, a finding that may relate to the fact that regular physical activity is important to well-being (Daley and Parfitt, 1996;Dubbert, 2002) and suggesting exercise may boost resources available to deploy to meet work and family commitments.…”
Section: Main Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, having children and being young increased travelers' WFC to some extent. These results are also in line with an earlier study concerning business 804 CDI 19,7 travelers ( Jensen, 2013) and others affected by WFC in general ( Jansen et al, 2003;Kinnunen et al, 2004). Furthermore, WFC was at a lower level among travelers who exercised regularly, a finding that may relate to the fact that regular physical activity is important to well-being (Daley and Parfitt, 1996;Dubbert, 2002) and suggesting exercise may boost resources available to deploy to meet work and family commitments.…”
Section: Main Findingssupporting
confidence: 90%
“…There are at least three earlier studies focussing on work-family or work-life interaction among IBTs ( Jensen, 2013;Mäkelä et al, 2015;Westman et al, 2008). Westman et al (2008) reported that the number of trips did not predict WFC but the level of WFC varied among women during pre-, on-and after-trip stages to an extent that was statistically significant.…”
Section: International Business Travel and Wfcmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional exhaustion manifests itself by the lack of energy, with emotional resources being fully consumed by work (Maslach, Jackson, Leiter, Schaufeli & Schwab, ). A similar association as that between work‐role conflict and emotional exhaustion has also been demonstrated between work‐family conflict and emotional exhaustion, (e.g., Geurts, Rutte & Peeters, ; Jensen, ).…”
Section: Introductionsupporting
confidence: 57%
“…In the US alone, $283B was spent on business travel in 2014. 84 However, such travel can be disruptive both to the business and the personal life of the traveler (Gustafson, 2012) including contributing to family conflict and burnout (Jensen, 2014). Nevertheless, for business (let alone personal and family relationships) face-to-face contact is thought to be essential.…”
Section: Remote Collaborationmentioning
confidence: 99%